Modernisasi Tungku Pembakaran di UMKM Djawadi Pande Besi Desa Gilangharjo: Modernization of the Furnace at the Djawadi Pande Besi located in Gilangharjo Village - Venditias Yudha; Angge Dhevi Warisaura; Ferriawan Yudhanto; Fajar Yulianto Prabowo (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The Djawadi blacksmiths are one of the groups of blacksmith craftsmen who are still productive and surviving amidst the youth's declining interest in continuing the business, which is the local wisdom of Gilangharjo Village. The priority problem currently being experienced by Djawadi blacksmiths is in the field of production. The forging work process at Djawadi blacksmith still uses simple equipment and has yet to apply science and technology or appropriate technology. The furnace is now made from concrete with an open design, making the combustion process less effective and causing air pollution. The aim of this activity is the modernization of environmentally friendly stoves. The method is carried out by designing a furnace with a closed system and considering ergonomic aspects. The results of the activity are the dissemination of environmentally friendly furnaces with a dust filtration system equipped with centrifugal fans and blowers.